Nutritional evaluation of millet at different seeding rates and cutting heights - Milke, Lilian Monise; Campana, Mariana; Antônio, Giovani; Morais, Jozivaldo Prudêncio Gomes de; Zilio, Elissandra Maiara de Castro; Santos, Juliana Aparecida Alves dos; Del Valle, Tiago Antonio (Brazilian Journal of Veterinary Research and Animal Science, 2018)
This study evaluated the effect of different seeding rates and cutting heights on production and composition of millet. Two randomized block design experiments were performed. In the first trial, 32 parcels (1.2 × 1.2 m) were used for evaluation of seeding rate of 24, 35, 50 and 60 kg/ha. Three cuts were carried out to evaluate plant height, fresh and dry mass yield, dry matter (DM), neutral detergent fiber (NDF), crude protein (CP) and acid detergent lignin (ADL) concentration and in situ DM and NDF digestibility. In the second trial, 20 parcels (1.2 × 3.0 m) were used to evaluate 20, 30, 40 and 50 cm of cutting heights for two growing cycles, performing the evaluations previously listed. Seeding rate linearly increased plant height, fresh and dry mass production, and tended to linearly decrease dry matter in situ digestibility, without effects on forage composition. Cutting height had no effect on crude protein (CP) concentration, but linearly increased plant height, dry mass production, DM content and tended to decrease NDF in situ digestibility and ADL content. Thus, the use of the highest evaluated seeding rates (60 kg/ha) and cutting height (50 cm) increased forage production; however, the use of the lowest residual height increased forage quality.